Pengaruh Partisipasi Anggota Terhadap Peningkatan Sisa Hasil Usaha (Shu) Pada Koperasi Simpan Pinjam (Ksp) Amsal Kupang Ntt - Yolanda O.M. Widyasari (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
Yolanda Widyasari. 2025. The Influence of Member Participation on the Increase of Business Result Surplus (SHU) in Amsal Kupang Savings and Loans Cooperative (KSP). The problem of this research is the low business result surplus at Amsal Kupang Savings and Loans Cooperative (KSP). The aim of this study is to (1) understand the description of member participation and the influence of member participation on the Business Result Surplus (SHU) in Amsal Kupang Savings and Loans Cooperative (KSP). The population in this study consists of financial report data from Amsal Kupang Savings and Loans Cooperative (KSP). The sample includes financial report data from 2020 to 2024. The research method used is simple linear regression analysis using quantitative data. Hypothesis testing is conducted through the t-test. The results of the t-test indicate that the independent variable does not have an effect on the dependent variable, thus it can be concluded that partially, the member participation variable does not affect SHU. The results of the coefficient of determination test show that 82.2% of the SHU variable is explained by the independent variable in this study (Member Participation as seen from the amount of savings). The remaining 7.8% of the SHU variable is explained by other external factors that are not included in this study.